2016
DOI: 10.17261/pressacademia.2016116558
|View full text |Cite
|
Sign up to set email alerts
|

Employment and exchange rate volatility relationship: the Turkish case

Abstract: In this paper, exchange rate volatility and employment relationship is investigated for Turkey covering the period from January 2003 to February 2014 period. Exchange rate volatility is added to the model as an independent variable. In the previous researches, effects of exchange rate volatility have been used as an error term. Different from the previous studies, we added this variable to our model as an independent variable in order to analyze the effects of volatility on employment. In empirical analysis; f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The results further indicated that negative effect becomes much more severe as export shares and leverage ratio increase. Ay and Ayhan (2016) found negative but statistically insignificant long run and short run impacts of exchange rate volatility on employment for Turkey over the period from 2003 to 2014. Their results showed presence of cointegration among employment, import, export, industrial production, real exchange rate and real exchange rate volatility.…”
Section: Effect Of Exchange Rate and Its Volatility On Labor Markets: Literature Reviewmentioning
confidence: 93%
See 2 more Smart Citations
“…The results further indicated that negative effect becomes much more severe as export shares and leverage ratio increase. Ay and Ayhan (2016) found negative but statistically insignificant long run and short run impacts of exchange rate volatility on employment for Turkey over the period from 2003 to 2014. Their results showed presence of cointegration among employment, import, export, industrial production, real exchange rate and real exchange rate volatility.…”
Section: Effect Of Exchange Rate and Its Volatility On Labor Markets: Literature Reviewmentioning
confidence: 93%
“…Previous empirical studies showed that exchange rate appreciation (depreciation) influence labor markets, significantly and negatively (positively) (see for example, Branson and Love, 1988;Edwards, 1989;Revenga, 1992;Burgess and Knetter, 1998;Gourinchas, 1998;Gourinchas, 1999;Goldberg and Tracy, 2000;Campa and Goldberg, 2001;Klein, Schuh and Triest, 2003;Bilgin, 2004;Ribeiro et al, 2004;Frenkel and Ros, 2006;Milas and Legrenzi, 2006;Galindo et al, 2007;Chang, 2010;Demir, 2010;Moser, Urban and di Mauro, 2010;Nucci and Pozzolo, 2010;Boz, 2013;Ayhan, 2016;Ay and Ayhan, 2016;Mpofu and Nikolaidou, 2018;Usman and Elsalih, 2018). In contrary to these studies, Berument, Dogan and Tansel (2006) and Bakhshi and Ebrahimi (2016) found that exchange rate devaluation and depreciation increase unemployment.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Employment in seven of the manufacturing R. C. Akkay industries indicates a positive response to the real appreciation while 18 of them show a negative response. Ay and Ayhan (2016) state the negative impact of the exchange rate volatility on the employment level. Alexandre (2017) finds out that the market rigidity decreases the exchange rate elasticity of employment in different industries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(Mishra et al 2014) 5. Ay and Ayhan (2016), and Usman and Elsalih (2018) use monthly data in their empirical researches.…”
Section: Business and Economicsmentioning
confidence: 99%